Sketching for architecture + interior design - Travis, Stephanie (London : Laurence King Publishing, 2015)
"Sketching for Architecture + Interior Design is an indispensable and practical guide for students wishing to master the art of looking and sketching. Forty-five step-by-step exercises take the student from the simple three-dimensional forms of furniture, through interiors, to complex building exteriors, and cityscapes. Technical topics covered include tools, line weight, perspective proportion, composition, shading, serial views, and context. Exercises are illustrated with beautiful sketches specially created by the author."--Cover.
Introduction -- Furniture + lighting -- Interiors -- Architecture -- Acknowledgements.
Keywords: Architectural drawing -- Technique; Drawing -- Technique